Histological variety of gastric carcinoma and Helicobacter pylori cagA and vacA polymorphism. Issue 9 (September 2015) - Figura, Natale; Valassina, Marcello; Moretti, Elena; Vindigni, Carla; Collodel, Giulia; Iacoponi, Francesca; Giordano, Nicola; Roviello, Francesco; Marrelli, Daniele
<x xml:space="preserve">Abstract</x> Background Helico bacter pylori infection may increase the risk of both histotypes of gastric carcinoma (GC): intestinal (IGC) and diffuse (DGC). Polymorphism of the main H. pylori virulence factors, cagA and vacA, could have a different impact on the histological variety of GC. Methods Two hundred and twenty-six H. pylori colonies were examined from 28 GC patients: 15 with IGC and 13 with DGC. DNA was extracted from bacteria and a PCR was performed using primers specific for cagA, the 3′ cagA variable region and s and m regions of vacA. Results There were 214 cagA+ strains and 55.61% of them were isolated from IGC cases; there were 12 cagA− colonies and they were all isolated from DGC (P<0.001). Most patients were infected by strains with more than one cagA structural type. No strains with a particular cagA type were found to be significantly more frequent in either histological variety of GC. A percentage of 43.90 of strains with vacA subtype s1/m1 were isolated from IGC, whereas 80.95% of vacA subtype s1/m2 strains were isolated from DGC cases (P<0.001). Conclusion Polymorphism of the main virulence genes of H. pylori may play different roles in the pathogenesis of IGC and DGC.